Urinary Neutrophil Gelatinase-associated Lipocalin in the evaluation of Patent Ductus Arteriosus and AKI in Very Preterm Neonates: a cohort study. Issue 1 (December 2017) - Sellmer, Anna; Bech, Bodil; Bjerre, Jesper; Schmidt, Michael; Hjortdal, Vibeke; Esberg, Gitte; Rittig, Søren; Henriksen, Tine
Abstract Background A patent ductus arteriosus (PDA) is frequently found in very preterm neonates and is associated with increased risk of morbidity and mortality. A shunt across a PDA can result in an unfavorable distribution of the cardiac output and may in turn result in poor renal perfusion. Urinary Neutrophil Gelatinase-associated Lipocalin (U-NGAL) is a marker of renal ischemia and may add to the evaluation of PDA. Our primary aim was to investigate if U-NGAL is associated with PDA in very preterm neonates. Secondary, to investigate whether U-NGAL and PDA are associated with AKI and renal dysfunction evaluated by fractional excretion of sodium (FENa) and urine albumin in a cohort of very preterm neonates. Methods A cohort of 146 neonates born at a gestational age less than 32 weeks werec onsecutively examined with echocardiography for PDA and serum sodium, and urine albumin and sodium were measured on postnatal day 3 and U-NGAL and serum creatinine day 3 and 6. AKI was defined according to modified neonatal Acute Kidney Injury Network (AKIN) criteria. The association between U-NGAL and PDA was investigated. And secondly we investigated if PDA and U-NGAL was associated with AKI and renal dysfunction. Results U-NGAL was not associated with a PDA day 3 when adjusted for gestational age and gender. A PDA day 3 was not associated with AKI when adjusted for gestational age and gender; however, it was associated with urine albumin. U-NGAL was not associated with AKI, but was found to be associated with urine albumin and FENa. Conclusions Based on our study U-NGAL is not considered useful as a diagnostic marker to identify very preterm neonates with a PDA causing hemodynamic changes resulting in early renal morbidity. The interpretation of NGAL in preterm neonates remains to be fully elucidated.